Psychosocial benefit and adherence of adolescents with chronic diseases participating in transition programs: a systematic review - Ravens Esther; Becker Johanna; Pape Lars; Ernst Gundula (De Gruyter, 2020)
Chronically ill young people must transition to the adult health care service after their 18th birthday. The transition from child centred paediatric care to the adult health care service is not simply limited to the change from familiar structures to something unknown, but includes the entire process of growing up, of individuals becoming independent from their parents and taking responsibility for their own disease management. Young people are at particular risk of losing the connection to medical care during this phase and the transition of young people with chronic conditions is associated with a high risk of declining adherence and worsening health status. Studies suggest that transition programs might be helpful, yet there is no evidence as to whether risks can be reduced or which intervention components are particularly conducive to better outcome. This study aimed to identify transition-specific interventions and evaluate their effect on the improvement of psychosocial parameters, such as health related quality of life and adherence of patients. A systematic literature review was conducted. Electronic databases (Cochrane, Embase, Pubmed, Web of Science) were searched by two independent reviewers for intervention studies aiming to improve transition. Grey literature was also searched. Studies were included if they evaluated transition-specific interventions aiming to improve psychosocial or adherence parameters of participants aged 12 years and older suffering from a chronic condition. Both controlled trials and studies with measurements before an after the intervention were included. The GRADE approach was used to assess the quality of evidence. The inclusion criteria was met by forty studies. Patients suffered from different chronic conditions, such as inflammatory bowel disease, type 1 diabetes or juvenile idiopathic arthritis. Transition interventions used several program components, such as transition coordinators, patient education programs or web-based interventions. Outcomes included quality of life, transition-specific knowledge, adherence and loss to follow up. Thirty-eight studies showed beneficial effects in the intervention group, respectively after intervention. The overall study quality was low. A large number of studies evaluating transition-specific interventions was included. Transition-specific interventions seem to have beneficial effects on psychosocial outcomes and adherence. The promotion of health literacy, appointment arrangement service and the use of technical elements (websites, SMS) seem to be particularly helpful in the transition process. As the patient population was diverse, the results can be transferred to other diseases. Even though the overall study quality was poor, it is possible to draw some conclusions. Future studies should aim to include large numbers of patients over extended periods of time in order to assess long-term outcomes.